Influence of molybdenum content on corrosion resistance and phase formation in alloy model Fe-Cr-Mo - Luis FlÃvio Gaspar Herculano (2011)
Currently the development of ferritic alloys Cr-Mo more resistant to corrosion at high temperatures has been much in demand. An alloy widely used in the petrochemical industry is the 9Cr-1Mo alloy. The objective of this work is to study the effect of molybdenum content in the formation of deleterious phases and corrosion resistance alloys model Fe-Cr-Mo making a comparison with the commercial alloy 9Cr-1Mo. We used a program to determine the thermodynamic solubilization temperatures and banding of deleterious phases at temperatures 450-650 Â C. It was found that the condition solubilized in the model alloys had a ferritic structure. The addition of molybdenum promotes the emergence of intermetallic phases, increasing the presence of the same temperature range. The analysis by different techniques show that the precipitates formed in 9Cr-1Mo alloy are the type M23C6. We observed the formation of a harmful phase rich in molybdenum, the alloys model from the temperature of 450 Â C. The phase found was characterized as the μ phase. The studied alloys tend to form a passivation film, but which are not stable. The 9Cr-1Mo alloy showed the worst corrosion resistance condition in relation to the model alloys. Molybdenum contents of more than 5% by weight, enable increased formation of deleterious phases and does not promote improvements in corrosion resistance. Key words: Molybdenum, potentiodynamic polarization, P9, μ phase